1991
DOI: 10.1073/pnas.88.10.4186
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type and e antigen-minus hepatitis B viruses and course of chronic hepatitis.

Abstract: Using an oligonucleotide hybridization assay, we studied the clinical implication of wild-type hepatitis B virus (HBV) and a HBV mutant that is unable to secrete hepatitis B e antigen (HBeAg) because of a translational defect due to a stop codon in the pre-C region in 106 hepatitis B surface antigen-positive patients with chronic hepatitis B. Wild-type HBV was detected in 31 of42 (73.8%) HBeAg-positive patients, whereas a mixed viral population was present in 10 (23.8%). Significant differences in the severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
237
4
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(259 citation statements)
references
References 25 publications
13
237
4
4
Order By: Relevance
“…7,15,16 In neonates born to HBsAg 1 /HBeAg 1 mothers, immune tolerance is further induced by transplacental passage of HBeAg that can result in specific tolerance of T helper cells to both HBeAg and HBcAg because these two antigens are crossreactive. 6,17 However, intrauterine infection and immunoprophylactic failure have also been reported in infants of HBsAg 1 /HBeAg 2 mothers. 7,18 Most studies of neonatal T-cell responses against HBV have focused on the immune responses elicited by HBsAg in vaccinated healthy infants.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,16 In neonates born to HBsAg 1 /HBeAg 1 mothers, immune tolerance is further induced by transplacental passage of HBeAg that can result in specific tolerance of T helper cells to both HBeAg and HBcAg because these two antigens are crossreactive. 6,17 However, intrauterine infection and immunoprophylactic failure have also been reported in infants of HBsAg 1 /HBeAg 2 mothers. 7,18 Most studies of neonatal T-cell responses against HBV have focused on the immune responses elicited by HBsAg in vaccinated healthy infants.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies found that A1896 emerges or is selected around the time of HBeAg seroconversion. 2,[5][6][7] These findings suggest that A1896 plays an important role in HBeAg clearance. However, not all patients develop A1896 after HBeAg seroconversion; some patients retain wild-type precore sequence, while others have undetectable HBV DNA in serum (by polymerase chain reaction [PCR] assay).…”
mentioning
confidence: 86%
“…[1][2][3][4][5][6][7] The predominant mutation involves a G-to-A change at nucleotide 1896 (A1896), which creates a premature stop codon at codon 28 ( Fig. 1).…”
mentioning
confidence: 99%
“…2,3 HBeAg-negative CHB is a potentially severe and progressive form of chronic liver disease with rare spontaneous remissions, frequent progression to cirrhosis, and increased risk of hepatocellular carcinoma (HCC). [4][5][6][7] The management of CHB has improved over the last years with the addition of lamivudine and more recently adefovir dipivoxil (ADV), but it is still suboptimal in achieving sustained off-therapy responses. [8][9][10][11] In particular in HBeAg-negative CHB, interferon-alfa (IFN␣), the first available effective therapeutic option in CHB, is the agent offering the higher chances for sustained-off therapy response ranging between 18% and 30%.…”
mentioning
confidence: 99%